1975
DOI: 10.1088/0022-3727/8/5/019
|View full text |Cite
|
Sign up to set email alerts
|

The optical constants of thin evaporated films of cadmium and zinc sulphides

Abstract: The optical constants n and k have been determined over the wavelength range from 2000-250 nm by measurements of reflectance and transmittance at normal incidence and treating these data by the method of Denton et al. (1972). The effects of surface roughness have been taken into account. Analysis of the dependence of absorption on photon energy have shown that the experimental results may be explained by the occurrence of direct transitions from 2.42 eV to 2.82 eV, in the case of CdS, followed by combined dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 17 publications
(18 reference statements)
5
27
0
Order By: Relevance
“…It has been reported that the intrinsic quality of CdS and CdSe films improves if deposited at elevated substrate temperatures. 17,18 The present observations show that the action of the ultrasonic vibrations of the substrate is similar to the case of depositing at elevated substrate temperature.…”
Section: B On Cdse Filmssupporting
confidence: 71%
“…It has been reported that the intrinsic quality of CdS and CdSe films improves if deposited at elevated substrate temperatures. 17,18 The present observations show that the action of the ultrasonic vibrations of the substrate is similar to the case of depositing at elevated substrate temperature.…”
Section: B On Cdse Filmssupporting
confidence: 71%
“…This wavelength lies below the band gap and ␣р10 4 cm Ϫ1 is noticeably smaller than it is at 476.5 nm. 5,6 Nonetheless only a weak transmission of Ϸ2% was measured and almost identical behavior to that in Fig. 2 was observed.…”
supporting
confidence: 77%
“…The comparison of standard and observed data is presented in Table 2. This shows a preferred orientation in film growth along (111) plane [19,20]. The grain size of these films was estimated using Scherrer formula by El-Kadry [21].…”
Section: Resultsmentioning
confidence: 99%